2022
DOI: 10.7150/thno.75069
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase-3 like-protein-1 promotes glioma progression via the NF-κB signaling pathway and tumor microenvironment reprogramming

Abstract: Background: Chitinase-3-like protein 1 (CHI3L1) is overexpressed in various types of tumors, especially in glioma, and contributes to tumor progression. However, the definite role of CHI3L1 and involved pathway in glioma progression are not completely understood. Methods: CHI3L1 expression in human gliomas and its association with patient survival was determined using enzyme-linked immunosorbent assay, western blot, immunohistochemistry, and public databases. Single-cell RNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…Chitinase-3-like protein-1 (CHI3L1), known as human homolog YKL-40, belonging to the glycoside hydrolase family, is highly expressed in various tumors, especially in GBM, and is involved in extracellular tissue remodeling, Th1/Th2 inflammation, oxidative injury, apoptosis, pyroptosis, angiogenesis, and parenchymal scarring [ 153 , 154 , 155 ]. CHI3L1 is highly expressed in glioblastoma and is related to poor patient prognosis.…”
Section: The Mechanism By Which M1- and M2-polarized Macrophages Prom...mentioning
confidence: 99%
“…Chitinase-3-like protein-1 (CHI3L1), known as human homolog YKL-40, belonging to the glycoside hydrolase family, is highly expressed in various tumors, especially in GBM, and is involved in extracellular tissue remodeling, Th1/Th2 inflammation, oxidative injury, apoptosis, pyroptosis, angiogenesis, and parenchymal scarring [ 153 , 154 , 155 ]. CHI3L1 is highly expressed in glioblastoma and is related to poor patient prognosis.…”
Section: The Mechanism By Which M1- and M2-polarized Macrophages Prom...mentioning
confidence: 99%
“…and NFKB. 58 CHI3L1 is released into the TME, interacts with CD44 expressed on tumour-associated macrophages, and activates the AKT pathway, thus promoting polarization of M2 macrophages. Genes like TMEM140 and GPX8 also play regulatory roles in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“… 57 Furthermore, the highly expressed CHI3L1 in gliomas enhances NF‐κB signalling by facilitating the translocation of NF‐κB subunits through binding to ACTN4 and NFKB. 58 CHI3L1 is released into the TME, interacts with CD44 expressed on tumour‐associated macrophages, and activates the AKT pathway, thus promoting polarization of M2 macrophages. Genes like TMEM140 and GPX8 also play regulatory roles in gliomas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Therefore, it is critical to investigate new prognostic indicators for glioma and identify other targets for treating this deadly disease. Studies have shown that nuclear factor κB (NF-κB) signaling pathway plays an important role in the development of glioma by mediating inflammation and immune response [ 58 ]. Silencing LOXL1-AS1 inhibit glioma cell proliferation and participate in regulating the NF-κB signaling pathway by inhibiting RELB directly [ 59 ].…”
Section: Role Of Loxl1-as1 In Various Cancersmentioning
confidence: 99%